2002
DOI: 10.1099/00207713-52-4-1361
|View full text |Cite
|
Sign up to set email alerts
|

Thermotoga lettingae sp. nov., a novel thermophilic, methanol-degrading bacterium isolated from a thermophilic anaerobic reactor.

Abstract: Thermotoga lettingae sp. nov., a novel thermophilic, methanol-degrading bacterium isolated from a thermophilic anaerobic reactor

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 45 publications
(38 reference statements)
3
58
0
Order By: Relevance
“…Very few SAOB have been successfully isolated and characterized to date. This limited collection is represented by only two thermophiles (T. phaeum and Thermotoga lettingae [51]), one that is thermotolerant (Tepidanaerobacter acetoxydans [19]), and two mesophiles (Clostridium ultunense [17] and Syntrophaceticus schinkii [52]). Recent studies have emphasized that the appearance of SAOB in anaerobic systems is more widespread than those characterized by culturedependent methods, and several genomes representing uncultured putative SAOB have been deduced (21,22,41).…”
Section: Discussionmentioning
confidence: 99%
“…Very few SAOB have been successfully isolated and characterized to date. This limited collection is represented by only two thermophiles (T. phaeum and Thermotoga lettingae [51]), one that is thermotolerant (Tepidanaerobacter acetoxydans [19]), and two mesophiles (Clostridium ultunense [17] and Syntrophaceticus schinkii [52]). Recent studies have emphasized that the appearance of SAOB in anaerobic systems is more widespread than those characterized by culturedependent methods, and several genomes representing uncultured putative SAOB have been deduced (21,22,41).…”
Section: Discussionmentioning
confidence: 99%
“…For C. ultunense, acetate oxidation using Fe(III) as an electron acceptor has been excluded [22,23]. In P. lettingae, acetate oxidation has been observed in the presence of thiosulphate [25]. In order to provide reduced ferredoxin for anabolic and catabolic pathways, both Rnf complex and Ech hydrogenases can reverse the electron flow using the electrochemical gradient and drive the thermodynamically unfavourable reduction of ferredoxin with NADH or hydrogen.…”
Section: Energy Conservation Associated With Saomentioning
confidence: 99%
“…However, our study revealed that at least two pathways for mesophilic acetate oxidation must exist, as the genome of C. ultunense lacks key enzymes of the WL pathway (Figure 4, 5). In the case of the thermophilic P. lettingae, the lack of WL pathway genes was expected, as the metabolism has been described as non-acetogenic [25] (Figure 4 All SAOB are potentially able to activate acetate to acetyl phosphate via acetate kinase ( Figure 4). In the case of S. schinkii and Th.…”
Section: Preprints (Wwwpreprintsorg) | Not Peer-reviewed | Posted: mentioning
confidence: 99%
See 2 more Smart Citations